ImmunoPEGliposome-mediated reduction of blood and brain amyloid levels in a mouse model of Alzheimer's disease is restricted to aged animals. (January 2017) - Ordóñez-Gutiérrez, Lara; Posado-Fernández, Adrián; Ahmadvand, Davoud; Lettiero, Barbara; Wu, Linping; Antón, Marta; Flores, Orfeu; Moghimi, Seyed Moein; Wandosell, Francisco
Abstract: The accumulation of extracellular amyloid-beta (Aβ) and intracellular neurofibrillary tangles (hyper-phosphorylated Tau) in the brain are two major neuropathological hallmarks of Alzheimer's disease (AD). Active and passive immunotherapy may limit cerebral Aβ deposition and/or accelerate its clearance. With the aid of a newly characterized monoclonal anti-Aβ antibody we constructed immunoPEGliposomes with high avidity for capturing Aβ in the periphery. The functionality of these vesicles in modulating Aβ uptake by both human brain capillary endothelial hCMEC/D3 cells (suppressing uptake) and THP-1 phagocytes (stimulating uptake) was confirmed in vitro. The multivalent immunoliposomes dramatically reduced circulating and brain levels of Aβ1-40, and particularly Aβ1-42, in "aged" (16 month-old), but not "adult" (10 month-old) APP/PS1 transgenic mice on repeated intraperitoneal administration. Furthermore, the immunoPEGliposome-mediated reduction in amyloidosis correlated with lower levels of glial fibrillary acidic protein (GFAP) and reactive glia (GFAP-positive cells). This treatment also lowered the ratio of phosphorylated Tau to total Tau. The therapeutic efficacy of immunoliposome treatment was superior to free monoclonal antibody administration (at an equivalent antibody dose). The potential mechanisms and significance of age-dependent immunoliposome therapy in AD is discussed.